Tradiciones discursivas en la historia del español americano. Difusión, contacto y desafíos - Garatea Grau, Carlos (2021)
The concept of discursive traditions today enjoys widespread consensus in the field of language history. This work offers some reasons and examples that justify its usefulness in the history of American Spanish and, in it, of the effects and expressions of contact with the indigenous languages of America. The purpose is simple: to appreciate the relevance of discursive traditions in the formation of American Spanish.